Effect of β-1,3-1,6-D-glukan (polysaccharide peptide) from miselia ganoderma lucidum extract as antioxidant and antiinflammation towards left ventricular systolic function in cardiometabolic patients - Aryanugraha, Teguh; Sargowo, Djanggan; Rahimah, Anna Fuji (Heart Science Journal, 2024)
Background: Cardiometabolic disease (CMD) describes a metabolic condition often associated with cardiovascular disease. It has been revealed that the Ganoderma lucidum polysaccharide peptide (GLPP) possesses anti-inflammatory and antioxidant qualities. Objective: This study aimed to find out how GLPP affected oxidative stress, inflammation, and left ventricular function in individuals with cardiometabolic syndrome.Methods: A multicenter double-blinded randomized controlled trial was carried out. Subjects with cardiometabolic syndrome received either GLPP or a placebo for ninety days. Before taking the initial treatment and one day following the last treatment intake, blood samples were taken from every participant. The enzyme-linked immunosorbent assay was used to evaluate the levels of serum tumor necrosis factor (TNF)-α, interleukin-6 (IL-6), malondialdehyde (MDA), and high-sensitivity-C-Reactive Protein (hs-CRP) while the colorimetric test was used to measure the levels of superoxide dismutase (SOD). Global longitudinal strain (GLS)  and Left ventricle ejection fraction (LVEF) were measured by single echocardiographer expert validation.Results: The MDA level was decreased in the GLPP treatment group (mean 56.0 ± 71.4 ng/mL to 27.7 ± 12.0 ng/mL, p= 0.023) compared to the control group (mean 39.3 ± 29.2 ng/mL to 38.3 ± 17.7 ng/mL, p= 0.719). However, the SOD level remained constant in the GLPP treatment (mean 122.2 ± 176.1 U/mL to 93.0 ± 40.9 U/mL, p=0.925) instead of significantly declining in the control group (mean 102.0 ± 67.3 U/mL to 64.0 ± 52.0 U/mL, p=0.016). The marker of TNF-α and hsCRP were significantly decreased in all groups (both p<0.05), but IL-6 was only significantly decreased in the control group (mean 1149.3 ± 581.7 pg/mL to 744.8 ± 336.5 pg/mL, p=0.010). The GLS was significantly decreased in the GLPP treatment group (-16.1 ± 4.1 to -17.5 ± 4.8, p=0.048) but there was no difference in LVEF in both groups (p>0.05).Conclusion: Patients with cardiometabolic syndrome may benefit from GLPP treatment for 90 days in terms of reduced inflammation, oxidative stress, and improved systolic left ventricular performance.